2017
DOI: 10.1007/s12223-017-0505-z
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of interaction between substrates/substrate analogs and benzoate 1,2-dioxygenase from benzoate-degrading Rhodococcus opacus 1CP

Abstract: Benzoate 1,2-dioxygenase (BDO) of Rhodococcus opacus 1CP, which carried out the initial attack on benzoate, was earlier shown to be the enzyme with a narrow substrate specificity. A kinetics of interaction between benzoate 1,2-dioxygenase and substituted benzoates was assessed taking into account the enlarged list of the type of inhibition and using whole cells grown on benzoate. The type of inhibition was determined and the constants of a reaction of BDO with benzoate in the presence of 2-chlorobenzoate (2CBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…Inducible enzymes benzoate 1,2-dioxygenase (BDO), 3-chlorobenzoate 1,2-dioxygenase (3-CBDO) and phenol hydroxylase (PH) initiated metabolism of benzoate (BA), 3-chlorobenzoate (3-CBA) and phenol (ph), respectively, in cells of this culture. For cells grown in LB medium (BA-, 3-CBA-and ph-free medium), no responses to the substrates (BA, 3-CBA and ph) were recorded with the use of the RMS formed on the basis of uninduced cells (the absence of inducible enzyme initiating substrate metabolism in cells of the culture-receptor) [16][17][18]. Using MMS based on uninduced cells, a response to the substrate of inducible enzyme was registered.…”
Section: Application Of the Rms Model For Assessment Of Biochemical A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Inducible enzymes benzoate 1,2-dioxygenase (BDO), 3-chlorobenzoate 1,2-dioxygenase (3-CBDO) and phenol hydroxylase (PH) initiated metabolism of benzoate (BA), 3-chlorobenzoate (3-CBA) and phenol (ph), respectively, in cells of this culture. For cells grown in LB medium (BA-, 3-CBA-and ph-free medium), no responses to the substrates (BA, 3-CBA and ph) were recorded with the use of the RMS formed on the basis of uninduced cells (the absence of inducible enzyme initiating substrate metabolism in cells of the culture-receptor) [16][17][18]. Using MMS based on uninduced cells, a response to the substrate of inducible enzyme was registered.…”
Section: Application Of the Rms Model For Assessment Of Biochemical A...mentioning
confidence: 99%
“…One of the modifications of BDO or 3-CBDO activity measurement is the polarographic determination with intact cells; the polarographic determination is similar to the measurement with the RMS formed on the basis of intact cells containing BDO or 3-CBDO. Not only the activities of BDO or 3-CBDO enzymes, but also the constants of enzyme inhibition by substrate-inhibitor, were determined with the RMS formed on the basis of Rhodococcus opacus 1CP induced cells [17,18,29]. For the types of inhibition described by Dixon et al [30], the calculation of constants of enzyme inhibition by substrate stems from the knowledge of the mechanisms of inhibition.…”
Section: Application Of the Laboratory Models Of The Microbial Sensor...mentioning
confidence: 99%
“…In the presence of the initiating enzyme both processes contribute to the formation of the response. It has been shown earlie [24] that the response of intact cells to a substrate depends on the presence of the cell enzymes that initiate substrate metabolism.…”
Section: Influence Of Ph and Type Of Buffermentioning
confidence: 99%
“…In majority of cases, the rate of BDO reaction is determined in whole cells by monitoring their respiration in the presence of respiration substrate [7]. We have shown that the change of freshly harvested cells respiration in the presence of benzoate was an indicator of BDO activity of R.opacus 1CP cells [8]. While studying growth of R. opacus 1CP on benzoate as a sole source of carbon we found that not only growth characteristics of the culture but also a kinetics of enzymatic reactions and the enzyme pool of the cell were changing when the benzoate concentration in the cultivation medium was raised [9; 10] …”
Section: Introductionmentioning
confidence: 98%